Kazakhstan and China: modern problems of the transfrontal rivers (International relations and international law Journal, 2016)
For Republic of Kazakhstan the use of water resources of the transfrontal rivers is the special and serious enough theme. On the estimations of experts, Kazakhstan is one and countries of the Eurasian continent, that largely is on the shortage of water resources. But to date Kazakhstan with all contiguous states have international agreements on the use and guard of transfrontal currents. However between Kazakhstan and China an agreement is absent on apportioning of water. In this connection, within the framework of the Kazakh-Chinese joint commission on the use and guard of the transfrontal rivers, the questions of collaboration are examined in the field of the use and to the guard of transfrontal currents and conclusion of treaty. Because, Peoples Republic of China, in turn, too are on the shortage of water resources and needs everything increasing their volumes for providing of necessities of industry, agriculture and supply of growing cities. In this context the question of settlement of water relations of Kazakhstan and China has the strategic setting for both states.
Keywords: transboundary rivers; transboundary rivers control; agreement; ecosystem; state; settlement; international cooperation